Managerial decision making - Moore, Don A. (Edward Elgar Publishing Ltd. CheltenhamGB, 2011)
Presents papers on behavioural decision research, i.e. it compares what is with what ought to be. Focuses on bounded rationality, anchoring, framing, overconfidence, fairness, strengths, weaknesses and idiosyncrasies of human intuitive judgement.